Sannikov S.V. ZNAKI PRISUTSTVIJA. KREŠČENIE V KONTEKSTE BAPTISTSKOJ SAKRAMENTOLOGII - Alikin, Valeriy (Bogoslovskie razmyšlenija, 2020)
BOOK REVIEW:Signs of the Presence: Baptism in the Contextof Baptist Sacramentology. Sannikov S.V. - Kiev.: SPIRIT I LITER, 1919. - 624 p. ISBN 978-966-378-669-8; 273.00 UAHThe book of Sergey Viktorovich Sannikov, widely known among the gospel sky Christian Baptists and other Protestant Slavs in the countries of the former USSR, is a unique study by Baptist Sacramentology on example of water baptism and is undoubtedly a significant contribution to an emerging galaxy of works devoted to the analysis of Baptist sacramentlism and evangelical-baptist theology in an eastern european context.